First Year Winner: Against All Odds: WRIT 1700A, Writing: Process and Practice. CD: Jon Sufrin - Clarke, Sonia (Jan Rehner Prize for Writing, 2023)
This self-reflection essay is both intimate and socially conscious, with a profound, sophisticated understanding of history, race, and the high stakes - and high rewards - of thinking deeply about your personal journey. The piece does an incredible job of placing us on the scene in the mid-1960s; the reader really feels like they are in the moment with the narrator, sitting with them in their classroom, walking with them down the streets of London, crying with them in the washroom. We were also highly impressed by the writer’s thoughtful, impactful use of secondary sources, and we think that the essay’s tone, structure, and message would be a perfect fit for a publication like The Globe and Mail, as per the prompt. We heartily commend the writer for their courageous, honest, and fiercely mature efforts here.